Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12940-016-0194-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal arsenic exposure and gestational diabetes and glucose intolerance in the New Hampshire birth cohort study

Abstract: BackgroundGestational diabetes mellitus (GDM) is a major pregnancy complication with detrimental effects for both mothers and their children. Accumulating evidence has suggested a potential role for arsenic (As) exposure in the development of GDM, but current studies have not assessed As exposure from water, urine or toenail samples.MethodsWe investigated the association between As exposure and risk of glucose intolerance and GDM among 1151 women enrolled in the New Hampshire Birth Cohort Study. Arsenic was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 50 publications
(55 reference statements)
3
50
0
Order By: Relevance
“…iAs is a naturally occurring element in the earth's crust and both humans and wildlife are exposed to iAs through food and water. Estimates of over 100-million people worldwide are exposed to levels exceeding World Health Organization (WHO)-established limits ( Adams et al, 2016 ; Farzan et al, 2016 ; Yang et al, 2009 ). The first prospective cohort study of people chronically exposed to arsenic has revealed an increase in all-cause and chronic disease mortalities ( Ahsan et al, 2006 ; Argos et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…iAs is a naturally occurring element in the earth's crust and both humans and wildlife are exposed to iAs through food and water. Estimates of over 100-million people worldwide are exposed to levels exceeding World Health Organization (WHO)-established limits ( Adams et al, 2016 ; Farzan et al, 2016 ; Yang et al, 2009 ). The first prospective cohort study of people chronically exposed to arsenic has revealed an increase in all-cause and chronic disease mortalities ( Ahsan et al, 2006 ; Argos et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, disease may also perturb elemental levels and alter the expression of other chemical compounds in the body [14]. A good example here includes the effect of arsenic exposure on the reduction of glucose tolerance [92]. Elemental dyshomeostasis in the body will also affect hair metabolic processes and hence elemental levels within the actively growing hair.…”
Section: Discussionmentioning
confidence: 99%
“…In the Maternal-Infant Research on Environmental Chemicals Study, the risk of GDM was nearly fourfold greater in the highest vs lowest tertile of dimethylarsinic acid levels [53]. Overall, arsenic has been associated with GDM in many [54][55][56][57] but not all studies [58]. In addition to disruptions during gestation, the dynamic changes that happen in the pancreatic islet under the influence of pregnancy hormones suggest that environmental insults that occur during this window may permanently reprogram beta cells and thereby alter their long-term function.…”
Section: Beyond Offspring: Impact Of Gestational Exposures On Mothersmentioning
confidence: 99%